Joint Modeling, Covariate Adjustment, and Interaction: Contrasting Notions in Risk Prediction Models and Risk Prediction Performance - Kerr, Kathleen F. (2011)
Epidemiologic methods are well established for investigating the association of a predictor of interest and disease status in the presence of covariates also associated with disease. There is less consensus on how to handle covariates when the goal is to evaluate the increment in prediction performance gained by a new marker when a set of predictors already exists. We distinguish between adjusting for covariates and joint modeling of disease risk in this context. We show that adjustment versus joint modeling are distinct concepts, and we describe the specific conditions where they are the same. We also discuss the concept of interaction among variables and describe a notion of interaction that is relevant to prediction performance. We conclude with a discussion of the most appropriate methods for evaluating new biomarkers in the presence of existing predictors.